Analysis of Soil Acceleration in The Mentawai Region with The Method Probabilistic Seismic Hazard Analysis (PSHA) - Matias Adam Canny Calvary Laia; - Syafriani (Department of Physics – Universitas Negeri Padang UNP, 2022)
The Mentawai Islands are one of the areas that are active in seismicity. An earthquake measuring 7.2 on the Richter scale on October 25, 2010 resulted in many casualties and material losses. Many buildings collapsed and facilities were damaged so that space managers needed a seismic hazard map to be able to organize the space by considering the disaster aspect. This prompted researchers to conduct research aimed at making seismic hazard maps and knowing the level of earthquake hazard in the Mentawai region. Seismic hazard maps are useful in planning earthquake-resistant buildings and can describe the effects of earthquakes at a location which will help in anticipating community preparedness and earthquake disaster mitigation efforts. Seismic hazard data processing uses the Probabilistic Seismic Hazard Analysis (PSHA) method. PSHA is based on earthquake parameters that produce the largest ground motion. The magnitude of the intensity at a location due to an earthquakein the earthquake source area with a magnitude of M and a distance of R, the attenuation function can be used. The attenuation functions in this study are Joyner-Boore (1997) and Young et al (1997). This type of research is descriptive, namely by collecting NEIC/USGS earthquake catalog data for the period 1950 - 2021 with M 5 SR.The results of this study indicate that the area of ywhich has a high level of seismic hazard is found in the Siberut area with a maximum PGA range of 1.17 g - 3.70 g. The area with a low seismic hazard level is the Pagai area with a PGA range of 0.80 g - 2.86 g. This result represents a 10% chance of being exceeded in 50 years.